HEMODYNAMIC STATUS STABILITY: BLOOD PRESSURE, MEAN ARTERY PRESSURE AND RESPIRATORY RATE IN ACUTE MYOCARDIAL INFARCTION PATIENTS IN CRITICAL CARE UNIT, SURAKARTA - Wulandari, Novita Kurnia; Widyaningsih, Tri Sakti; Kanita, Maria Wisnu (Postgraduate Program , Poltekkes Kemenkes Semarang, 2024)
The most important monitoring of acute myocardial infarction patients is monitoring the hemodynamic system because it affects the function of oxygen delivery in the body and involves heart function. This research aimed to find out the condition of the stability of blood pressure, mean artery pressure and respiratory rate in Acute Myocardial Infarction patients in the critical care unit, Surakarta. The method used an analytical observation design with a cross-sectional approach. The samples were 56 subjects. The results show statistical tests of respiratory aids, namely nasal cannula and non-rebreathing mask on hemodynamic status including systolic, diastolic blood pressure, mean artery pressure, and respiratory rate in the critical care unit, Surakarta, there is a significant relationship between the use of respiratory aids and hemodynamic status as evidenced by the value (p value <0.05). The conclusion suggests that it’s better the fulfillment of oxygen therapy needs with the proper respiratory aids (nasal cannula and non-rebreathing mask, the better the patient's hemodynamic status, especially in terms of blood pressure, mean artery pressure, and respiratory rate which are important indicators in the stability of acute myocardial infarction patients.